Estado cognitivo y nivel educativo en el adulto mayor del centro diurno “La Providencia” en el cantón Catamayo, periodo 2022. - Paladinez Peña, Lisbeth Stefania (2022)
The cognitive status of older adults is a topic of concern to the authorities of the day care center "La Providencia" in the canton of Catamayo because in recent months there have been difficulties like lack of orientation, lack of memory, and lack of understanding among the elderly. This results in difficulties for these people to carry out their daily activities normally. In view of this problem, the present work of curricular integration intends to analyze what circumstances limit the cognitive state and educational level of the older adults of the mentioned center, and above all to propose a solution that proposes a series of activities capable of improving the daily coexistence of the older adults. The following methods were used: scientific, hypothetical-deductive, inductive, deductive, analytical-synthetic, statistical, which allowed to fulfill each of the research phases. Last but not least, the techniques of interview and data tabulation of the mini mental test instrument were applied. As for the results of the objectives, we can determine that with regard to the first objective, most of the older adults have a low cognitive state, while no one has a severe state. In the second objective, most of the respondents have completed basic elementary education, while the minority have reached high school. In the third objective, which refers to the relationship between the cognitive status and the educational level of the older adults, it is determined that there is a relationship. Finally, it can be concluded that most of the older adults presented mild cognitive impairment, with respect to their dimensions of orientation in time, orientation in space, language/nomination/comprehension and fixation; therefore, it is recommended that cognitive stimulation strategies be implemented to help improve these difficulties. Palabras claves: <cognitive development><cognitive reserve> < vygotsky's theory>< piaget's theory>